اثر التعليم المدمج في تعليم مهارتي المناولة والاخماد بكرة القدم لطلبة الصف الثاني متوسط (Journal of the College of Basic Education, 2022)
The aim of the current research is to study the impact of blended learning and teaching football skills to students of the second intermediate grade, through the preparation of an educational program and it was presented to the experts.In the second chapter, the researcher dealt with theoretical studies, and the third chapter included field research procedures, as the research community was chosen by the intentional method from the students of Baghdad Education Schools, Al-Rusafa, the third - Al-Amana Intermediate School for Boys - the second grade average, as the total research community reached (187) students, distributed on (5) People As for the research sample, the researcher conducted a lottery to select (20) students from them in a random way, and after arranging them in ascending order, they were divided in a systematic random way into two groups (experimental and control) and by (10) students from Division (C) as an experimental group and ( 10) Students from Hall (D) as a control group The educational program was applied to the experimental research sample and lasted for eight weeks with two educational units per week, thus the total educational units amounted to (16) educational units, and then the researcher conducted post tests for the experimental and control groups. And the results were treated statistically between the post tests of the experimental and control groups. The results of the tests showed that there were significant differences between the results of the pre and post tests for the control and experimental groups, and the emergence of significant differences between the results of the post tests for the experimental and control groups and in favor of the results of the post tests. The results of the study were presented and discussed.In the fifth chapter, the conclusions reached by the researcher were presented by showing an effective impact on the impact of blended learning in teaching the skill of soccer scoring for second-grade students. It was recommended that similar studies be conducted in different games and different age groups